Substantive feasibility of the implementation of the final product development of ecolinguistic learning model in the perspective of green ecology - Rahardi, R. Kunjana (Universitas Ahmad Dahlan, 2023)
Damage to the natural environment caused by exploitation, deforestation and uncontrolled deforestation is also a major concern. The Indonesian Language Education Study Program at the Masters Program, Sanata Dharma University has included the Ecolinguistics course since its establishment in 2015. The purpose of this research was formulated as follow: Describe the feasibility of developing a Naturalistic Ecolinguistic learning model in the perspective of Green Ecology. The research and development steps follow the model proposed by Borg and Gall consisting of the following stages: a) The initial stage involves research and data collection by collecting relevant information to formulate a product design framework. b) The planning stage involves making a product development plan. c) The product draft development stage involves the initial development of the ecolinguistic learning model design. d) The initial field trial phase involved limited field trials to collect data to be used as a basis for product design revisions. e) The main product revision stage. f) The main field trial phase involves a wider trial of the ecolinguistic learning model design product. g) The product improvement stage based on field test results involves product design improvements based on input from field trials. h) The field implementation test phase involves testing the product design. i) The final product improvement stage. j) The dissemination and implementation phase focuses on disseminating the ecolinguistic learning model. The research results showed that 43% of respondents stated that it was suitable for use with revisions according to the notes and 57% of respondents stated that it was suitable for use without revisions. Thus, it can be concluded that the ecolinguistic learning model for the Indonesian Language Education Masters Program is feasible to implement without revision.